Aging photosynthetic bacteria monitored by absorption and fluorescence changes - Asztalos, Emese; Kis, Mariann; Maróti, Péter (Acta Biologica Szegediensis, 2010)
Production and arrangement of photosynthetic pigments into protein complexes were monitored by steady state and kinetic absorption and fluorescence methods in different phases of growth curve of photosynthetic purple bacterium Rhodobacter sphaeroides. The increase of the number of pigments (B800, B850 and B875) followed that of the cells and could be described by the modified Gompertz equation. The newly synthesized chromophores were imbedded immediately into the proteinous scaffold independently on the age of the cell (no free pigments were observed). The assembly, however, showed age-dependent changes manifested by slight ( 5 nm) blue-shift of the absorption peak of B875 in LH1, by small increase ( 10%) of the variable fluorescence and by increased duration of the electrochromic shift detected at 525 nm. The observed changes of the organization of the bacteriochlorophylls in the photosynthetic units upon aging the cell correspond to the tendency of more efficient capture and utilization of light energy.